Impact of the Global Financial Crisis on Migration and Remittances - Mohapatra, Sanket; Ratha, Dilip (World Bank, Washington, DC, 2012)
Remittances to developing countries are estimated to have declined by 6.1 percent in 2009 as a result of weak job markets in major destination countries. Although new migration has fallen, it is still positive. The stock of international migrants, therefore, has continued to grow and remittances have remained resilient. Going forward, remittance flows to Latin America are expected to recover, whereas those to East Asia and South Asia are likely to slow. Policy responses should involve efforts to facilitate migration and remittances to make these flows cheaper, safer, and more productive for both the sending and the receiving countries.